Enhancing the Quality-Of-Service Management for Managers and Frontline Employees: The Case of Post Office Services, South Africa - Eposi, Elsie Mbua (International Review of Management and Marketing, 2024)
This study examined the factors that could assist in improving service quality for postal customers who residents and reside in the postal areas in an endeavour to establish an effective service management quality for postal services. A qualitative research method was applied which enhanced the collection of data through semi structured interviews from managers and frontline employees. Data was transcribed and was analysed using Atlas-ti (Version 8.1). Results obtained from the study reveals that effective strategic implementation, effective training and development, motivation, as well as an effective monitoring and evaluation system are the most influential components to use in improving the quality of services within post offices. Other factors identified include maintaining distinctive strategic positioning, using e-business technology to improve efficiency and competitive advantage, maintaining effective support from top management, putting emphasis on the quality of service offer by frontline employer’s during operations, and maintaining good parcel system security, creating an effective communication system; consistency in improving services; instilling confidence and trust among consumers; fostering special treatment to consumers; and the provision of high-quality services. Based on the findings, it is recommended that management of the postal sector should provide adequate and quality services to customers, through an effective strategic implementation plan, effective training and development, motivation, as well as an effective monitoring and evaluation system, maintaining distinctive strategic positioning, using e-business technology to improve efficiency and competitive advantage, maintaining effective support from top management, putting emphasis on the quality of service offer by frontline employer’s during operations, and maintaining good parcel system security, creating an effective communication system; consistency in improving services; instilling confidence and trust among consumers; fostering special treatment to consumers; and the provision of high-quality services.